Romeo and Juliet - Olson, Rebecca (Open textbook library., 2021)
This edition of Romeo and Juliet was edited by students for students. We believe that reliably edited versions of the play should be available for free online. But we wanted ours to be easy to get in other ways as well. The editors—Oregon State University students who remember, far better than their professors, what it was like to read the play for the first time—carefully considered every pronoun, punctuation mark, and footnote. Our goal: to make a friendly, confidence-building edition that supported classroom activities at the high school and college level.